ISOLATION AND CHARACTERIZATION OF COLLAGEN FROM SNAKEHEAD (CHANNA STRIATA) SKIN WITH DIFFERENT SOLVENTS AND SOAKING TIME - ACE BAEHAKI; SHANTI D. LESTARI; AHMAD AMRINSYAH (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The objective of this research was to utilize snakehead skin waste as an alternative source of collagen. Different solvents (acetic acid, chloride acid and citric acid) and different soaking time (three days and five days) were employed as treatments in this study. Parameters observed were yield, protein solubility, and molecular weight. The results showed that acetic acid is the optimal solvent for extracting the snakehead skin collagen as indicated by the highest yield with an average value of 84.07 %. The collagen with highest protein solubility was produced by soaking the snakehead skin in acetic acid for 5 days. The results of SDS-PAGE analysis revealed 14 kinds of protein in a collagen. Each different solvent produced collagen with various molecular weights which ranged from 12.39 to 185.70 kDa.